RETRACTED: How maritime logistic SMEs lead and gain competitive advantage by applying information technology? - Dean Luo; Muhammad Saeed Shahbaz; Muhammad Asif Qureshi; Maira Anis; Farhan Mahboob; Hayfa Kazouz; Jie Mao (Frontiers in Psychology)
The aim of this study was to examine the importance of information technology for logistics Small Medium Entreprise (SMEs) in Pakistan. It is the time of technological rapidness; especially after COVID-19, the word business has majorly transformed into a digital business. If an organization did not shift toward technology, it would be hard for it to even sustain in this rapid era. This study adopts the questionnaire after extensive literature review. A quantitative study was conducted among logistics SMEs in Pakistan to empirically verify what competitive advantages they are leading and gaining from information technology and how much information technology is important for their sustainability. The literature lacks information about the ways in which information technology has been integrated into logistics SMEs operating model, and more specifically, there is no information about IT valence, IT resource commitment, IT managerial commitment, and IT competency. The research is primarily quantitative in nature, where the data were collected via a close-ended questionnaire from 340 logistics SMEs in Pakistan. The independent variable of this research was information technology (i.e., IT valence, IT resource commitment, IT managerial commitment, and IT competency), whereas the dependent variable was competitive advantage. The study found that IT had a significant impact on the competitive advantage of logistics SMEs operating in Pakistan. All the variables related to IT had a significant impact on competitive advantage, which included IT valence, IT resource commitment, IT managerial commitment, and IT competency. This study helps managers and owners of logistics SMEs in decision-making, who can understand how much IT can enhance their performance and reduce their risks. This study has been specifically conducted with logistics SMEs operating in Pakistan, which means that there is much scope to be worked upon, i.e., by selecting companies operating in other countries and comparing them with current findings. This study observes the impact of information technology (i.e., IT valence, IT resource commitment, IT managerial commitment, and IT competency) on competitive advantage, and other independent variables can be studied to find the impact on competitive advantage.